Four decades of World Natural Heritage – how changing protected area values influence the UNESCO label - Conradin, Katharina; Engesser, Matthias; Wiesmann, Urs (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
Since the launch of the World Heritage Convention in 1972, World Heritage sites have become increasingly popular. To date, more than 1000 sites have received World Heritage status, among them 228 natural and mixed sites. Yet too, in the past four decades, protected area paradigms have evolved from rather strict and exclusionary to more integrative approaches. Nevertheless, relatively little is known on how such developments influence World Natural Heritage (WNH) sites. This paper presents the results of a global survey of 128 of 211 WNH sites listed in 2011 and analyses the results by taking the year of inscription as a reference. The article shows that the understanding of WNH status has undergone great changes: from being perceived as an internationally valued instrument to foster conservation, WNH status has now rather become a label of great promotional importance. This can, e.g., be shown by a decreasing influence of WNH status on the status of protection of a site. Conversely, the influence of WNH status on visitor numbers has increased with time. Furthermore, evidence suggests that more complex effects of WNH status attribution, such as a site’s influence on sustainable development, take time to develop and are thus greater for sites that have been inscribed in the list at an earlier date. Given these developments, it is necessary to rethink whether the World Heritage approach in its current form is still timely, and how the development potential of World Natural Heritage sites can be tapped while ensuring their conservation.